Structural, mechanical, and electronic properties of nanotubes based on buckled arsenene: A first-principles study. (March 2020) - Chen, Bo; Xue, Lin; Han, Yan; Li, Xiang-Qian; Yang, Zhi
Highlights: Buckled arsenene nanotubes are stable and as stiff as silicon and black phosphorene nanotubes. Electronic properties of buckled arsenene nanotubes can be modulated by uniaxial strain. Faceted nanotubes can be constructed by introducing defects lines or joining buckled and puckered arsenenes. Abstract: At present work, the structural, mechanical, and electronic properties of zigzag and armchair buckled arsenene nanotubes are investigated using density functional theory. All nanotubes are found to be stable by means of vibrational spectra and room temperature molecular dynamics simulations. With the enlargement of tube diameter, armchair nanotubes are energetically more favorable than zigzag nanotubes at first and then the strain energies of both zigzag and armchair nanotubes are about the same; Young's modulus increases in general and zigzag nanotube is stiffer than the armchair one with a comparable diameter; Poisson ratio is relatively insensitive to tube diameter at the beginning and decreases about one order of magnitude for zigzag nanotubes, while the Poisson ratio of armchair nanotubes has a opposite behavior. Zigzag nanotubes and some armchair nanotubes with small diameter exhibit an indirect band gap, whereas the armchair nanotubes with larger diameter exhibit a direct band gap. Transition between indirect to direct band gap or semiconductor to metal is tunable by uniaxial strain, and the effective mass of electron is smaller than that of hole. In particular, faceted nanotubes could be constructed by introducing defect lines or joining different structural phases of arsenene.